Residual strain measurement based on longitudinal to shear wave velocity ratio with a dual-mode EMAT - Dang, Geng; Pei, Cuixiang; Yang, Zhanfeng; Zhou, Haiqiang (Frontiers in Materials, 2023)
In this paper, a new and noncontact method with measuring longitudinal to shear wave velocity ratio by a dual-mode electromagnetic acoustic transducer (EMAT) is proposed for residual strain measurement in a metal structure without knowing its thickness. Firstly, the theoretical derivation of the ratio of longitudinal and shear wave velocities in electromagnetic ultrasound was conducted, and based on this, the effectiveness of the dual-mode bulk wave electromagnetic acoustic transducer was simulated.Secondly, the longitudinal and shear wave velocities of uniaxial stretched aluminum plates with different residual strains were measured using the established electromagnetic ultrasound experimental system.Finally, the ratio of longitudinal and shear wave velocities of specimens with different plastic deformations was analyzed, achieving quantitative non-destructive testing of residual strain in uniaxial tensile aluminum plates.